Highly dispersed Ru nanoclusters anchored on B, N co-doped carbon nanotubes for water splitting. Issue 5 (1st February 2022) - Fan, Meihong; Chen, Xinran; Zhang, Mingcheng; Cui, Lili; He, Xingquan; Zou, Xiaoxin
Abstract : Ultrafine dispersed ruthenium nanoparticles on B, N-co-doped carbon nanotubes with simultaneously optimized nanostructures and electronic property were developed to achieve a high catalytic activity for both HER and OER. Abstract : Boron and nitrogen co-doped carbon nanotubes (CNTs)were developed as a substrate material for the loading of 2–3 nm uniform Ru clusters. Combined with a theoretical and experimental comparison, it was confirmed that B doping as well as its synergistic effect with N-doping in CNTs can effectively reduce the adsorption energy of the H intermediate at Ru site, improving the catalytic activity of the Ru cluster/CNT material for the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Benefiting from the synergistic effect of multi element doping and a porous tubular structure, the as-formed Ru@B, N-CNTs show excellent electrocatalytic activity for both HER and OER in alkaline conditions. An overpotential of 54 mV and 315 mV is needed to achieve a current density of 10 mA cm −2, which exceeds requirements for commercial Pt/C and RuO2 . Furthermore, when assembled into an electrolyzer with Ru@B, N-CNTs as both the anode and the cathode, the cell requires a cell voltage of only 1.57 V to drive a current density of 10 mA cm −2 in an alkaline medium and has excellent catalytic stability for over 40 hours.